2002
DOI: 10.1128/jb.184.7.1932-1939.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of CAMP Cohemolysin as a Potential Virulence Factor of Riemerella anatipestifer

Abstract: Riemerella anatipestifer is responsible for exudative septicemia in ducks. The genetic determinant of the CAMP cohemolysin, cam, from a strain of R. anatipestifer was cloned and expressed in Escherichia coli. Chromosomal DNA from serotype 19 strain 30/90 was used to construct a gene library in pBluescript II SK(؊) vector in E. coli XL-1-Blue strain. The clones containing recombinant plasmids were screened for the CAMP reaction with Staphylococcus aureus. Those that showed cohemolysis were chosen for further an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 26 publications
1
48
0
Order By: Relevance
“…Genomic DNA extracted from R. anatipestifer strain RA0511 was partially digested by Sau3A, ligated into BamHI digested pBluescript II SK(() vector and subsequently transformed into Escherichia coli XL1-Blue (Crasta et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA extracted from R. anatipestifer strain RA0511 was partially digested by Sau3A, ligated into BamHI digested pBluescript II SK(() vector and subsequently transformed into Escherichia coli XL1-Blue (Crasta et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Riemerella anatipestifer is a Gram-negative, non-motile, non-spore-forming, rod-shaped bacterium (Crasta et al, 2002) belonging to the Flavobacteriaceae family in the rRNA superfamily V (Subramaniam et al, 1997). It is the causative agent of duck septicaemia (Segers et al, 1993), a contagious disease of domestic ducks, turkeys, and various other bird species.…”
Section: Introductionmentioning
confidence: 99%
“…anatipestifer is an avian pathogen of ducks and turkeys, and it is a major economic burden in the duck industry worldwide (Huang et al, 1999;Ryll et al, 2001;Pathanasophon et al, 2002;Sarver et al, 2002;Cheng et al, 2003). Limited information about the molecular basis of the pathogenesis is available for this organism, and so far only two potential bacterial virulence or virulence-associated gene have been identified (Weng et al, 1999;Crasta et al, 2002). Determination of bacterial genes differentially expressed during infection in the host may provide valuable information for increasing our understanding of pathogenesis of R. anatipestifer.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only two potential virulence factors, VapD and CAMP, have been identified. The data showed that VapD has some homology to virulence-associated proteins from other bacteria (Weng et al, 1999) and that CAMP cohaemolyin has high homology to those of O-sialoglycoprotein endopeptidases (Crasta et al, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…Despite the devastating losses it causes to the duck industry, not much is known about the pathogenesis of R. anatipestifer infection and its virulence factors (Weng et al, 1999;Crasta et al, 2002;Zhou et al, 2009). The reported R. anatipestifer whole genome sequence should facilitate the understanding of disease mechanisms of this pathogen (Zhou et al, 2011).…”
Section: Introductionmentioning
confidence: 99%